Study of New Contractive Conditions of Integral Type and Fixed Point Theorems in Cone Metric Space - Kumar, Deepak (Current Topics on Mathematics and Computer Science Vol. 4, 2021)
The aim of this paper is to extend the concept of F. Khojasteh, Z. Goodarzi and A. Razani to some new contractive conditions of integral type in cone metric space.